2010
DOI: 10.1177/1753425909350057
|View full text |Cite
|
Sign up to set email alerts
|

Antiserum against Raoultella terrigena ATCC 33257 identifies a large number of Raoultella and Klebsiella clinical isolates as serotype O12

Abstract: Raoultella terrigena ATCC 33257, recently reclassified from the genus Klebsiella, is a drinking water isolate and belongs to a large group of non-typeable Klebsiella and Raoultella strains. Using an O-antiserum against a capsule-deficient mutant of this strain, we could show a high prevalence (10.5%) of the R. terrigena O-serotype among non-typeable, clinical Klebsiella and Raoultella isolates. We observed a strong serological cross-reaction with the K. pneumoniae O12 reference strain, indicating that a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 68 publications
2
11
1
Order By: Relevance
“…The R. terrigena O-antigen shares the same repeating unit (and serological cross-reactivity) with the K. pneumoniae O12 antigen, where the same repeat unit polysaccharide is terminated with a single ␤-Kdo residue at the nonreducing terminus (37). Signals consistent with this terminator were reported in the NMR spectrum of R. terrigena O-antigen (31). The sequence data are consistent with WbbB partici- pating in both chain extension and chain termination, but this remains to be confirmed biochemically, and the precise activities giving rise to the O-antigen backbone are not central to the current study.…”
Section: Generation Of Recombinant Strains Expressing the O-antigen Fsupporting
confidence: 66%
See 3 more Smart Citations
“…The R. terrigena O-antigen shares the same repeating unit (and serological cross-reactivity) with the K. pneumoniae O12 antigen, where the same repeat unit polysaccharide is terminated with a single ␤-Kdo residue at the nonreducing terminus (37). Signals consistent with this terminator were reported in the NMR spectrum of R. terrigena O-antigen (31). The sequence data are consistent with WbbB partici- pating in both chain extension and chain termination, but this remains to be confirmed biochemically, and the precise activities giving rise to the O-antigen backbone are not central to the current study.…”
Section: Generation Of Recombinant Strains Expressing the O-antigen Fsupporting
confidence: 66%
“…4, bottom panel, and Table 1), as well as the 1 H, 13 C heteronuclear single-quantum coherence spectrum of the O-antigen expressed in CWG1218 (⌬wzx-wbbK ⌬gtrA) and comparison with data reported previously (31), confirmed that it possesses a disaccharide repeat unit structurally identical to that of the R. terrigena ATCC 33257 and K. pneumoniae O12 O-antigen (Fig. 1).…”
Section: Elucidation Of the Structures Of R Terrigena O-antigens Expsupporting
confidence: 58%
See 2 more Smart Citations
“…and RP has been investigated finding that both, Klebsiella pneumoniae and RP, have type 1 fimbriae and mannosesensitive haemagglutination; furthermore Klebsiella spp. have the ability to resist the bactericidal effects of human serum, a feature that is shared by RP (Mertens et al 2010).…”
Section: Introductionmentioning
confidence: 99%